Regional Strain Score as Prognostic Marker of Cardiovascular Events From the Multi-Ethnic Study of Atherosclerosis (MESA) - Pezel, Theo; Bluemke, David A.; Wu, Colin O.; Lima, João A. C.; Ambale Venkatesh, Bharath (Frontiers in Cardiovascular Medicine, 2022)
BACKGROUND: Left ventricular (LV) circumferential strain (Ecc) is an accurate indicator of regional myocardial function, particularly using the regional Ecc or layer-specific strain. AIM: This study aimed to investigate the prognostic value of a regional strain score (RSS) for predicting the incident of heart failure (HF) and coronary heart disease (CHD) in a population without a history of cardiovascular disease at baseline. MATERIALS AND METHODS: Data from participants in the Multi-Ethnic Study of Atherosclerosis (MESA) who underwent tagged magnetic resonance imaging for strain determination were analyzed. Using −17% and −10% as Ecc cut-offs, each segment was rated from 0–2 points according to the Ecc value of each layer. The endo-Ecc, mid-Ecc, and epi-Ecc values from the 16-segment model were used to calculate three RSS: Endo-, Mid-, and Epi-RSS, respectively, which were defined as a percentage of good LV regional function. The Intramyocardial-RSS was the sum of these three RSS. Cox proportional hazard models were used to evaluate the association between each RSS and incident HF and hard CHD. RESULTS: Among the 1,506 participants (63.3±9.4 years, 54.6% men), 122 cases of hard CHD and 91 cases of HF were observed (median [IQR] follow-up 15.9 [12.9-16.6] years). After adjustment, Mid-, Epi-, and Intramyocardial-RSS values <50% were independently associated with HF (adjusted HR 1.43; 95% CI [1.08-2.87], p=0.004; HR 1.80; 95% CI [1.12-3.07], p<0.001; and HR 2.01; 95% CI [1.19-3.20], p<0.001). After adjustment, Endo-, Mid-, Epi-, and Intramyocardial-RSS <50% were also independently associated with hard CHD (adjusted HR 1.31; 95% CI [1.03-1.51], p=0.04; HR 1.79; 95% CI [1.26-2.57], p<0.001; HR 2.03; 95% CI [1.45-3.40], p<0.001; and HR 2.28; 95% CI [1.51-3.53], p<0.001). CONCLUSIONS: Layer-specific regional Ecc, assessed by RSS, provides a robust, independent predictive value for incident HF and hard CHD in asymptomatic participants without any history of previous clinical cardiovascular disease. Clinical Trial Registration: Unique identifier: NCT00005487.